Patients Satisfaction about Magnetic Resonance Imaging Services at Combined Military Hospital, Dhaka - Rahman, Md Rezaur; Munir, Umar Rashed; Zafreen, Farzana; Wahab, Md Abdul (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: MRI investigation indicates sensitivity as well as specificity. The increasing clinical utility, coupled with the greater availability and capacity to per¬form, has resulted in a dramatic increase in their use over the past de¬cades. The expectation of the care seekers has also increased and it is a major concern whether this increase in MRI result has improved patient outcomes or not. Objective: The study was carried out with the aim to evaluate various aspects of satisfaction among the MRI performing patients at Combined Military Hospital, Dhaka. Materials and Methods: This descriptive cross sectional study was carried out on patient satisfaction of MRI services at CMH, Dhaka. A total of 186 patients performing investigation at MRI Department of CMH Dhaka since 01st May 2011 to 15th May 2011 were interviewed. Data were collected and analysed by face-to-face interview and reviewing medical record with the help of a questionnaire and checklist. Results: The waiting time of 8-12 weeks for MRI was maximum among 24.7% patients; followed by 17.7% for 2-4 weeks and 16.1% for 1-2 weeks. It also revealed that waiting time was higher (8-12 weeks) in Neurosurgery referred cases (33.3%), Orthopaedic (28.2%) followed by Neurology (14.3%) (p<0.05). The outdoor patients experienced more waiting time in comparison to indoor patients. Orthopaedic referred cases had the highest (53.8%) positive finding followed by Neurosurgery (15.1%) and Medicine (7.5%). A significant majority of the patients are satisfied (68.81%) or very satisfied (25.80%) with the MRI service. Conclusion: This study finding will help the hospital administrator not only in monitoring the investigation but also to take measures to improve the facilities of MRI department. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 61-63